Uses and gratifications of problematic mukbang watching - The role of eating and social gratification: A pilot study - Kircaburun, Kagan; Savci, Mustafa; Emirtekin, Emrah; Griffiths, Mark D. (Pergamon-Elsevier Science Ltd, 2022)
[Abstract Not Available]
Keywords: Mukbang; Eating; Food; Social; Eating disorder; Food addiction